Existence and General Decay Estimates for a Petrovsky-Petrovsky Coupled System with Nonlinear Strong Damping - Beniani, Abderrahmane; Bahri, Noureddine; Zennir, Khaled (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we consider a coupled system of Petrovsky-Petrovsky equations with nonlinear dissipative terms. We proved the existence and stability of solution to the coupled system (1) under some assumptions (7)-(9) based on the work [1]. The approach adopted is the Faedo-Galerkin method. Furthermore, by applying the multiplier method and some weighted integral inequalities, we strictly proved the decay properties (23).